2004
DOI: 10.1074/jbc.m311805200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Yeast Cytochrome bc1 Complex by Ilicicolin H, a Novel Inhibitor That Acts at the Qn Site of the bc1 Complex

Abstract: Ilicicolin H is an antibiotic isolated from the "imperfect" fungus Cylindrocladium iliciola strain MFC-870. Ilicicolin inhibits mitochondrial respiration by inhibiting the cytochrome bc 1 complex. In order to identify the site of ilicicolin action within the bc 1 complex we have characterized the effects of ilicicolin on the cytochrome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 26 publications
(41 reference statements)
2
53
0
Order By: Relevance
“…The in vitro mode-of-action of ilicicolin was nicely identified to the yeast cytochrome bc1 reductase of Complex III of the mitochondrial electron transport chain. [49][50][51] Activity of the mammalian enzyme was unaffected, indicating that the compound is fungal-specific. Depending upon the fungal species, MICs ranged from 0.04-1.56 mg/mL.…”
Section: Preclinical Compounds: a Mitochondrial Inhibitormentioning
confidence: 96%
See 1 more Smart Citation
“…The in vitro mode-of-action of ilicicolin was nicely identified to the yeast cytochrome bc1 reductase of Complex III of the mitochondrial electron transport chain. [49][50][51] Activity of the mammalian enzyme was unaffected, indicating that the compound is fungal-specific. Depending upon the fungal species, MICs ranged from 0.04-1.56 mg/mL.…”
Section: Preclinical Compounds: a Mitochondrial Inhibitormentioning
confidence: 96%
“…None of the compounds mentioned above target mitochondria except ilicicolin, discussed below. [49][50][51] Ilicicolin is a CIII fungal-specific inhibitor…”
Section: Preclinical Compounds: a Mitochondrial Inhibitormentioning
confidence: 99%
“…However, compounds that retained the general molecular shape of ilicicolin H, for example, hydrazones 6−8 and corresponding pyrazoles 9−11, lost only 10−20-fold antifungal activity as compared to compounds with significant change in the molecular shape (e.g., 2−5), which lost >250-fold activity (Table S4 in the Supporting Information). It appears that the retention of the shape is not sufficient for the retention of the activity, for example, the oxadiazocine (12), oxime (13), and isoxazole (14) did not show any activity at 10000 ng/mL. The whole cell activity SAR and the fungal reductase activity SAR did not track well.…”
mentioning
confidence: 99%
“…In contrast, antimycin showed no selectivity in this assay with IC 50 values of 0.5, 0.5, and 0.1 ng/mL, respectively, against C. albicans MY1055 and rat and rhesus NADH:cytochrome c oxidoreductase. Independent studies by Gutierrez et al 14 showed >70-fold selectivity for the yeast ubiquinol: cytochrome c reductase (S. cerevisiae) as compared to the bovine reductase (IC 50 = 87−108 ng/mL, 200−250 nM).…”
mentioning
confidence: 99%
See 1 more Smart Citation